2016
DOI: 10.1097/hrp.0000000000000092
|View full text |Cite
|
Sign up to set email alerts
|

The Longitudinal Course of Schizophrenia Across the Lifespan

Abstract: Supplemental digital content is available in the text.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
84
1
4

Year Published

2017
2017
2024
2024

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 134 publications
(94 citation statements)
references
References 70 publications
5
84
1
4
Order By: Relevance
“…It is characterized by positive symptoms, such as delusions and hallucinations, and by negative phenotypes, including impaired cognitive function and social abilities (2,3). A number of genes have been associated with the risk to develop schizophrenia (4)(5)(6).…”
Section: Hdac1 Links Early Life Stress To Schizophrenialike Phenotypesmentioning
confidence: 99%
“…It is characterized by positive symptoms, such as delusions and hallucinations, and by negative phenotypes, including impaired cognitive function and social abilities (2,3). A number of genes have been associated with the risk to develop schizophrenia (4)(5)(6).…”
Section: Hdac1 Links Early Life Stress To Schizophrenialike Phenotypesmentioning
confidence: 99%
“…While individual variations occur, cognition is commonly compromised in people with schizophrenia (Galletly et al ., ). Meta‐analysis of eight studies comparing cognitive performance between people with schizophrenia and healthy controls found that people with schizophrenia performed more poorly at baseline and over time (Heilbronner, Samara, Leucht, Falkai & Schulze, ).…”
Section: Introductionmentioning
confidence: 99%
“…Longitudinal descriptions, such as those emerging from the Chestnut Lodge Study and its follow-up studies, have also relied on this concept [3, 4], and a recent comprehensive review on the course of schizophrenia relied on psychopathological studies that used the positive-negative approach [5]. Lately, a new system-specific approach has been proposed to bridge the gap between clinical psychopathology and neurobiological research [6].…”
Section: Introductionmentioning
confidence: 99%